Hubungan Status Gizi dengan Kelelahan Kerja Pada Karyawan di PT. X - Syifa Farha; Linda Riski Sefrina; Miliyantri Elvandari (Jurnal Ilmiah Wahana Pendidikan, 2022)
Fatigue is a condition that is felt by every individual that can cause work accidents and even death, fatigue symptoms for each individual are different but centered on loss of efficiency and decreased capacity as well as endurance, work fatigue is caused by several factors, one of which is nutritional status. This study aims to determine the relationship between nutritional status and work fatigue on employees at PT X. The sample is 92 employees, data collection uses, observations, interviews, questionnaires and literature studies. Hypothesis testing using the Spearman Rank test. The results of the study there was no relationship between nutritional status and work fatigue on employees at PT. X